Honoring Women in the Prohibition of Divorce: An Exploration of Legal Pluralism in Marriage Among the Indigenous People of Cireundeu, Indonesia - Sofiana, Neng Eri; Neng Eri Sofiana (Center of Gender Studies and Child of State Islamic Institute of Metro, 2025)
State and Islamic law allow divorce as an alternative mechanism or way out of bad relations in marriage, in accordance with the rules. It is even referred to as an emergency exit. However, this is different from the Cireundeu traditional group, where divorce is prohibited. There is no divorce mechanism found in this traditional marriage. This article explores the philosophical and sociological reasons related to the phenomenon of divorce prohibitions, while viewing it through the lens of legal pluralism. The research method used is qualitative research with data obtained from interviews conducted with elders and public relations for traditional groups, as well as data from documentation in the form of written notes attached to the regulations. Therefore, philosophically and sociologically, the Cireundeu traditional group is an indigenous community that adheres to customs and respects women’s rights. This is proven by prohibition of divorce as a form of loyalty, mutual protection and love until death do us part. In practice, the different legal arrangements for divorce illustrate Indonesia’s legal pluralism. [Hukum negara dan hukum Islam memperbolehkan perceraian sebagai mekanisme alternatif atau jalan keluar dari hubungan pernikahan yang buruk, sesuai dengan aturan yang berlaku. Bahkan, perceraian sering disebut sebagai “pintu keluar darurat.” Namun, hal ini berbeda dengan kelompok tradisional Cireundeu, di mana perceraian dilarang. Tidak ada mekanisme perceraian yang ditemukan dalam pernikahan tradisional ini. Artikel ini mengeksplorasi alasan filosofis dan sosiologis terkait fenomena larangan perceraian, sambil memandangnya melalui lensa pluralisme hukum. Metode penelitian yang digunakan adalah penelitian kualitatif dengan data diperoleh dari wawancara dengan para sesepuh dan hubungan masyarakat kelompok tradisional, serta data dari dokumentasi berupa catatan tertulis yang melekat pada peraturan. Oleh karena itu, secara filosofis dan sosiologis, kelompok tradisional Cireundeu merupakan komunitas asli yang mematuhi adat dan menghormati hak-hak perempuan. Hal ini dibuktikan dengan larangan perceraian sebagai bentuk kesetiaan, perlindungan mutual, dan cinta hingga maut memisahkan kita. Dalam praktiknya, perbedaan pengaturan hukum terkait perceraian menggambarkan pluralisme hukum di Indonesia].